2018
DOI: 10.3390/molecules23030584
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Improves Heat Tolerance in Kiwifruit Seedlings through Promoting Antioxidant Enzymatic Activity and Glutathione S-Transferase Transcription

Abstract: Evidence exists to suggest that melatonin (MT) is important to abiotic stress tolerance in plants. Here, we investigated whether exogenous MT reduces heat damage on biological parameters and gene expression in kiwifruit (Actinidia deliciosa) seedlings. Pretreatment with MT alleviates heat-induced oxidative harm through reducing H2O2 content and increasing proline content. Moreover, MT application raised ascorbic acid (AsA) levels and the activity of antioxidant enzymes, including superoxide dismutase (SOD), ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
64
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(72 citation statements)
references
References 63 publications
(61 reference statements)
7
64
1
Order By: Relevance
“…antioxidant enzymes such as SOD, CAT, POD, and APX. Differences in antioxidant enzyme responses to melatonin treatment in our results compared with the results of Liang et al (2018) could be due to the different species used for the studies and the differences in plant maturity (mature plant vs. seedlings). Treatments that were associated with improved antioxidant content also influenced fatty acid content in leaf tissues.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…antioxidant enzymes such as SOD, CAT, POD, and APX. Differences in antioxidant enzyme responses to melatonin treatment in our results compared with the results of Liang et al (2018) could be due to the different species used for the studies and the differences in plant maturity (mature plant vs. seedlings). Treatments that were associated with improved antioxidant content also influenced fatty acid content in leaf tissues.…”
Section: Discussioncontrasting
confidence: 60%
“…No major differences were found for APX and CAT in response to melatonin treatment and heat stress. Liang et al (2018) found reduced H 2 O 2 content in melatonin treated kiwifruit (Actinidia deliciosa) seedlings and greater activity of many of the Fig. 2.…”
Section: Discussionmentioning
confidence: 92%
“…At the same time, MT treatment soluble protein content in kiwifruit were slightly higher than CK, Under adversity stress or aging process, the accumulation of free radicals, reactive oxygen species, lipid free radicals induced membrane lipid peroxide, eventually lead to cell damage or death. MDA is the final product of membrane lipid peroxidation, through the determination of its content may know the extent of the membrane lipid oxidative damage, so as to determine antioxidant capacity of plant (Liang et al, 2018). The results of this experiment showed that the content of MDA in kiwifruit decreased significantly with the treatment of melatonin, which improved the antioxidant ability of fruit to a certain extent.…”
Section: Discussionmentioning
confidence: 80%
“…Wild type started autotrophic growth at this timepoint already, with a high activity of peroxidase (Csa4G285740) and chlorophyll A-B binding protein (Csa3G664560), while albino mutant still needed to utilize the storage because it is still not able to photosynthesize resulted from a lack of functional chloroplast. Glutathione S-transferase have been reported mainly function in response to biotic and abiotic stresses, such as oxidative stress (55), high/low temperature stress (56,57) and different pathogen invasion (58)(59)(60). As well, a high concentration of glutathione S-transferase resulted in decreased chlorophyll content (61).…”
Section: Discussionmentioning
confidence: 99%